Tephrostratigraphy and Magma Evolution Based on Combined Zircon Trace Element and U-Pb Age Data: Fingerprinting Miocene Silicic Pyroclastic Rocks in the Pannonian Basin - Lukács, Réka; Guillong, Marcel; Bachmann, Olivier; Fodor, László; Harangi, Szabolcs (Frontiers in Earth Science, 2021)
We present a novel approach to use zircon as a correlation tool as well as a monitor for magma reservoir processes in silicic volcanic systems. Fingerprinting eruption products based on trace element content and U-Pb dates of zircon offers a promising, previously underestimated tephra correlation perspective, particularly in cases where the main minerals and glass are altered. Using LA-ICP-MS analyses, a rapid and cost-effective method, this study presents U-Pb dates and trace element concentration data of more than 950 zircon crystals from scattered occurrences of early to mid-Miocene silicic ignimbrites in the northern Pannonian Basin, eastern-central Europe. This magmatic phase produced >4000 km3 of erupted material, which provide unique stratigraphic marker horizons in central and southern Europe. The newly determined zircon U-Pb eruption ages for the distal pyroclastic deposits are between 17.5 and 14.3 Ma, comparable with the previously published ages of the main eruptive events. Multivariate discriminant analysis of selected trace element concentrations in zircon proved to be useful to distinguish the main volcanic units and to correlate the previously ambiguously categorized pyroclastic deposits with them. Using the zircon trace element content together with published glass data from crystal-poor ignimbrites, we determined the zircon/melt partition coefficients. The obtained values of the distinct eruption units are very similar and comparable to published data for silicic volcanic systems. This suggests that zircon/melt partition coefficients in calc-alkaline dacitic to rhyolitic systems are not significantly influenced by the melt composition at >70 wt% SiO2 at near solidus temperature. The partition coefficients and zircon trace element data were used to calculate the equilibrium melt composition, which characterizes the eruption products even where glass is thoroughly altered or missing. Hence, our results provide important proxies for tephrostratigraphy in addition to yielding insights into the complex processes of silicic magma reservoirs.